(untitled) (Afaq Lughawiyyah, 2024)
Ancient and contemporary scholars were interested in topics of semantics to determine the objectives of the discourse, what is noticeable - despite the abundance of works - is the lack of probing studies that include all the topics of semantics. Hence, the researchers chose to trace the connotations of the word “shar ” in the noble Prophet’s hadith, to clarify the lexical, terminological, contextual, and pivotal connotations of the word “shar” and its derivatives in the noble prophetic hadith , in an attempt to identify the thread regulating these connotations The researcher adopted the descriptive analytical approach; to realize these indications, by collecting information from its perspectives, extrapolating it, and analyzing it, in order to reach objective scientific results. The research concluded with several results, including: the occurrence of thirteen contextual indications for the substance “evil” and its derivatives in the random sample chosen from the noble Hadith of the Prophet, including: temptation and the most severe punishment of people, infidels, polytheism, injustice and corruption, harm, calamities, and so on. These indications were embodied in two pivotal indications for this article, namely: spread and intensity.